Fractal characteristics of nano-pores in the Lower Silurian Longmaxi shales from the Upper Yangtze Platform, south China. (December 2016) - Ji, Wenming; Song, Yan; Jiang, Zhenxue; Meng, Mianmo; Liu, Qingxin; Chen, Lei; Wang, Pengfei; Gao, Fenglin; Huang, Hexin
Abstract: To better understand the fractal characteristics of nano-pore structure and their effects on methane adsorption in marine shales, we have conducted ultra-low pressure nitrogen adsorption, methane adsorption, X-ray diffraction (XRD), total organic carbon (TOC), and vitrinite reflectance for eleven shale samples of the Lower Silurian Longmaxi Formation from the Upper Yangtze Platform, south China. Two fractal dimensions D1 and D2 (at relative pressures of 0–0.5 and 0.5–1, respectively) were obtained using the fractal Frenkel–Halsey–Hill (FHH) method based on low-pressure nitrogen adsorption isotherms. The relationships among composition of the Longmaxi shale (TOC, clay minerals, brittle minerals), the pore structure parameters (i.e. average pore diameter, surface area, pore volume), and the fractal dimensions were investigated. The results show that the Longmaxi shale possesses fractal geometries with fractal dimension D1 values ranging from 2.3542 to 2.4715 and fractal dimension D2 values ranging from 2.5818 to 2.7497. The good positive correlation between fractal dimensions D1 and the BET surface area and the strongly negative relationship between fractal dimensions D2 and the average pore diameter indicate that D1 can adequately characterize pore surface fractal dimension, while D2 represents the pore structure fractal dimension. Organic matter has a positive influence on the BET surface area and the BJH pore volume and a negative effect on the average pore diameter. The BJH pore volume and the average pore diameter have a positive relationship trend with the clay minerals content, whereas a negative linear trend with the brittle minerals content. The mineralogical compositions and TOC of the Longmaxi shale have different impacts on the pore structures, which in turn exert different effects on the fractal dimensions D1 and D2 . Both the fractal dimensions D1 and D2 have positive effects on the Langmuir volume of methane adsorption. However, the fractal dimensions D1 and D2 have opposite influence on the Langmuir pressures of methane adsorption. Thus the fractal dimensions can well be used to evaluate gas shale reservoir and shale gas accumulation in south China. Graphical abstract: Highlights: Pore structures of Longmaxi shale were investigated using N2 adsorption analysis. Fractal dimensions D1 and D2 were obtained at different at different relative pressure range. Fractal dimensions D1 and D2 have different relationships with shale composition and pore structure. Shale samples with a higher fractal dimension have greater methane adsorption capacity. Fractal dimensions D1 and D2 have different effects on the Langmuir pressure of methane adsorption.